The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/om9011104
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Selectivity in Intermolecular Alkene or Aldehyde Hydroacylation Reactions Catalyzed by {Rh(L2)}+Fragments

Abstract: Rhodium(III) dihydrido complexes [Rh(L 2 )(H) 2 (acetone)][BAr F4 ] (Ar F =C 6 H 3 (CF 3 ) 2 ) containing the potentially hemilabile ligands L 2 = 9,9-dimethyl-4,5-bis(diphenylphosphino)xanthene (Xantphos) and [Ph 2 P(CH 2 ) 2 ] 2 O (POP 0 ) have been prepared from their corresponding norbornadiene rhodium(I) precursors. In solution these complexes are fluxional by proposed acetone dissociation, which can be trapped out by addition of MeCN to form [Rh(L 2 )(H) 2 (NCMe)][BAr F 4 ], which have been crystallograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 67 publications
8
76
0
Order By: Relevance
“…These data are consistent with rapid inversion of the Xantphos ligand on the NMR timescale in solution, possibility via a k 3 eintermediate [12]. Similar NMR data are observed for the analogous Rhenorbornadiene complex [13].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These data are consistent with rapid inversion of the Xantphos ligand on the NMR timescale in solution, possibility via a k 3 eintermediate [12]. Similar NMR data are observed for the analogous Rhenorbornadiene complex [13].…”
Section: Resultssupporting
confidence: 83%
“…We have recently reported upon this unusual k 3 coordination mode using Rh-based systems, e.g. A [13], and were interested in extending this to iridium to afford complexes that are directly analogues to IrePNP systems that have found much recent application in CeH activation chemistry [14e18]. We report here a preliminary study into their synthesis and reactivity.…”
Section: Introductionmentioning
confidence: 98%
“…Cooling of 3 (183 K, CD 2 Cl 2 ) did not result in a 1 H NMR spectrum that reflects the solid-state structure (i.e., inequivalent hydrides were not observed). This is in contrast to [Rh(κ 3 -P,O,P -Xantphos)(H) 2 (acetone)][BAr F 4 ], 15 in which the hydrides are equivalent at 298 K but inequivalent at low temperature, which is suggested to be due to reversible decoordination of acetone. Given these data, we suggest that complex 3 exists in C 6 H 5 Cl or CD 2 Cl 2 solution predominantly as [Rh(κ 3 -P,O,P -Xantphos-3,5-C 6 H 3 (CF 3 ) 2 )(H) 2 ][BAr F 4 ], 2b, but can be recrystallized from C 6 H 5 Cl solvent to give the solvent adduct 3.…”
Section: Synthesis Of Rh(i) Precursor Complexesmentioning
confidence: 62%
“…[6] An alternative approach is to increase the rate of reductive elimination of ketone product, as tep that is often (although not exclusively [7] )t he turnover-limiting process in hydroacylation. [3a,8] Wide-bite-angle,o rs terically bulky,l igands have this effect, but also change the ratio of alkene versus aldehyde hydroacylation [9] or the linear/branched selectivity.…”
mentioning
confidence: 99%
“…[6] An alternative approach is to increase the rate of reductive elimination of ketone product, as tep that is often (although not exclusively [7] )t he turnover-limiting process in hydroacylation. [3a,8] Wide-bite-angle,o rs terically bulky,l igands have this effect, but also change the ratio of alkene versus aldehyde hydroacylation [9] or the linear/branched selectivity. [10] Additionally,these systems in general still require high loadings,a nd activated alkenes or terminal alkynes as substrates.S mall-bite-angle phosphine ligands,R 2 PCH 2 PR 2 (e.g.,R= t Bu, Cy), initially developed by Hofmann et al, [11] have been shown to favor the products of reductive elimination [12] and we recently demonstrated that catalyst systems exemplified by [Rh(R 2 PCH 2 PR 2 )(h…”
mentioning
confidence: 99%